IMPROVING STUDENTS’ LEARNING OUTCOMES THROUGH JIGSAW LEARNING MODEL AT GRADE VI SD NEGERI 066050 MEDAN - Mangara Halomoan Siagian; Ester Julinda Simarmata; Reflina Sinaga; Patri Janson Silaban (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
The learning model refers to a learning that encourages students to be active and help each other in mastering the subject. This study aimed to improve students’ learning outcomes at grade VI SD Negeri 066050 Medan Denai for the academic year 2020/2021. This research was Classroom Action Research. The results of the study revealed that for the pretest,6 students (23.07%) reached the target score with an average score of 63.45. In cycle I, there were 11 students (42.30%) who reached the target, with an average of 67.94%. In cycle II, there were 21 students (84.61%) who reached the target with an average of 82.56%. The learning implementation was categorized as good. This was seen from the results of observations of teachers’ activities in cycle I for 64% and in cycle II it increased to 82%. Then, the implementation of learning was good. This was seen from the results of students’ observation activities in cycle I for 60% and in cycle II it increased to 88%. Thus, the results of the study showed an increase in students’ learning outcomes on the theme of Bumiku, the sub-themes of Earth, the Sun and the Moon of learning 1 and learning 2 at grade VI SD for the academic year 2020/2021 . In short, implementing Jigsaw learning model improved students’ learning outcomes.